Cross-functional knowledge management the international landscape - Shams, S. M. Riad 1979- (The annals of business research, 2019)
Diverse kinds of knowledge are vital for each organization that would successfully compete today in an international scenario. The emergent relevance of knowledge and its management in an even more complex environment opens up the possibility to analyze, investigate and deepen our understanding on different aspects related to several functional areas in business management. Nowadays, firms that create new knowledge and apply it effectively and efficiently will be successful at creating competitive advantages. The choices of the firms in selecting and applying different knowledge process (such as knowledge sourcing, transferring and exploiting) as well as knowledge tools may be crucial. Thus, the role of knowledge as the key source of potential advantage for organizations and indeed whole economies is still a hot debate in the international landscape. This book develops insights for the management of knowledge in cross-functional business areas to originate an innovative approach to the classical Knowledge Management (KM) field. This book provides a fresh perspective on different knowledge related topics in an international landscape, highlighting the key role of knowledge and its management in business activities. Overall, the primary aim of this book is to extend our understandings on how KM can be helpful in several cross-functional management areas, such as strategic management, finance, HRM and innovation as well as in different business circumstances such as M & A, internationalization processes and risk management